Analisis Peran Norma Hukum Dalam Mempertahankan Kestabilan Negara - Esra Natasya Br Sitepu; Ivana Theo Philia; Jekson Saragih; Manotar Sinaga; Muthiah Latifah; Delva Fitria (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research is entitled " Analysis of the Role of Legal Norms in Defending State Stability" This research was carried out with the aim of finding out the actual role of legal norms in maintaining state stability. The method used in this research is a qualitative approach literature study research method. This research is useful for developing scientific insight into norms as a means of assessing the operation of law in society and the role of legal norms in maintaining state stability.